I have a query about how GroupHomomorphismByImages works.
In the listing below Q,P are copies of D4 with Q an fp-group
and P a permutation group. When mapping Q to P there is only
one way to express the images of the generators. In the reverse
direction the image of generator (1,2,3,4) is listed
(surprisingly to me) as f.2^-1*f.1^-2*f.2^-1 rather than f.1
(although, of course, these are equal).
(Sorry if this is a trivial query, but I am a new user.)
Chris Wensley
----------------------------- GAP listing ---------------------------------- LogTo("invmap.log"); Print("Isomorphisms between copies of dihedral D4\n\n"); f := FreeGroup(2, "f"); relQ := [ f.1^4, f.2^2, (f.1*f.2)^2 ]; Q := f/relQ; genQ := Q.generators; oQ := Size(Q); elQ := Elements(Q); Print("Q has generators: ", genQ, " and elements:\n", elQ, "\n\n"); P := Group( (1,2,3,4), (1,3) ); genP := P.generators; P.name := "P"; oP := Size(P); elP := Elements(P); Print("P has generators: ", genP, " and elements:\n", elP, "\n\n"); isoQP := GroupHomomorphismByImages(Q,P,genQ,genP); Print(" x isoQP(x) \n"); Print("--------- ---------- \n"); for j in [1..oQ] do x := elQ[j]; Print(x, " ", Image(isoQP,x), "\n"); od; invPQ := InverseMapping(isoQP); Print("\n x invPQ(x) \n"); Print("-------- ---------- \n"); for j in [1..oP] do x := elP[j]; Print(x, " ", Image(invPQ,x), "\n"); od; ---------------------------- Output ------------------------------------
Isomorphisms between copies of dihedral D4
Q has generators: [ f.1, f.2 ] and elements: [ IdWord, f.1, f.2, f.1^2, f.1*f.2, f.2*f.1, f.1^3, f.1^2*f.2 ] P has generators: [ (1,2,3,4), (1,3) ] and elements: [ (), (2,4), (1,2)(3,4), (1,2,3,4), (1,3), (1,3)(2,4), (1,4,3,2), (1,4)(2,3) ] x isoQP(x) --------- ---------- IdWord () f.1 (1,2,3,4) f.2 (1,3) f.1^2 (1,3)(2,4) f.1*f.2 (1,2)(3,4) f.2*f.1 (1,4)(2,3) f.1^3 (1,4,3,2) f.1^2*f.2 (2,4) x invPQ(x) -------- ---------- () IdWord (2,4) f.2^-1*f.1^-2 (1,2)(3,4) f.2^-1*f.1^-1 (1,2,3,4) f.2^-1*f.1^-2*f.2^-1*f.1^-1 (1,3) f.2^-1 (1,3)(2,4) f.2^-1*f.1^-2*f.2^-1 (1,4,3,2) f.1^-1 (1,4)(2,3) f.2^-1*f.1^-3